Modeling the Function of TATA Box Binding Protein in Transcriptional Changes Induced by HIV-1 Tat in Innate Immune Cells and the Effect of Methamphetamine Exposure - Tjitro, Ryan; Campbell, Lee A.; Basova, Liana; Johnson, Jessica; Najera, Julia A.; Lindsey, Alexander; Marcondes, Maria Cecilia Garibaldi (Frontiers in Immunology, 2019)
Innate immune cells are targets of HIV-1 infection in the Central Nervous System (CNS), generating neurological deficits. Infected individuals with substance use disorders as co-morbidities, are more likely to have aggravated neurological disorders, higher CNS viral load and inflammation. Methamphetamine (Meth) is an addictive stimulant drug, commonly used by HIV+ populations. The molecular basis of HIV direct effects and its interactions with Meth in host response, at the gene promoter level, are not well understood. The main HIV-1 peptide acting on transcription is the transactivator of transcription (Tat), which promotes replication by recruiting a Tata-box binding protein (TBP) to the virus long-terminal repeat (LTR). We tested the hypothesis that Tat can stimulate host gene, by also promoting TBP binding to Tata-box binding motifs. Genes with Tata-box domains are mainly inducible, involved in inflammation, regulation and metabolism, and relevant in HIV pathogenesis. We also tested whether Tat and Meth interact to trigger Tata-box bearing genes. The THP1 macrophage cell line is responsive to Tat, as well as to Meth, by recruiting RNA Polymerase (RNA Pol) to inflammatory gene promoters within 15 minutes of stimulation. Integrative consensus sequence analysis in genes with enriched RNA Pol, revealed that TBP was a major transcription factor in Tat stimulation, while the co-incubation with Meth shifted usage to a distinct and diversified pattern. For validating these findings, we engineered a THP1 clone to be deficient in the expression of all major TBP splice variants, and tested its response to Tat stimulation, in the presence or absence of Meth. Transcriptional patterns in TBP-sufficient and deficient clones confirmed TBP as a dominant transcription factor in Tat stimulation, capable of inducing genes with no constitutive expression. However, in the presence of Meth, TBP was no longer necessary to activate the same genes with Tata-box motifs, suggesting alternative promoter plasticity. These findings demonstrate TBP as mechanism of host-response activation by HIV-1 Tat, and suggest that promoter plasticity is one of the challenges imposed by co-morbid factors such as Meth. This may be one mechanism responsible for limited efficacy of therapeutic approaches in HIV+ Meth abusers.